The Current and Future Role of Microbial Culture Collections in Food Security Worldwide - Díaz-Rodríguez, Alondra María; Salcedo Gastelum, Lilian Alejandra; Félix Pablos, Carmen María; Parra-Cota, Fannie Isela; Santoyo, Gustavo; Puente, Mariana Laura; Bhattacharya, Dhruba; Mukherjee, Joydeep; de los Santos-Villalobos, Sergio (Frontiers in Sustainable Food Systems, 2021)
Food security is the pillar of nutritional wellbeing for food availability, and is necessary to satisfy all physiological needs to thus maintain the general wellbeing of populations. However, global agricultural deficiencies occur due to rapid population growth, causing an increase in competition for resources; such as water, land, and energy, leading to the overexploitation of agro-ecosystems, and the inability to produce a suitable quantity of efficient food. Therefore, the development of sustainable agro-biotechnologies is vital to increase crop yield and quality, reducing the negative impacts caused by intensive non-sustainable agricultural practices. In this way, the genetic and metabolic diversity of soil and plant microbiota in agro-ecosystems are a current and promising alternative to ensure global food security. Microbial communities play an important role in the improvement of soil fertility and plant development by enhancing plant growth and health through several direct and/or indirect mechanisms. Thus, the bio-augmentation of beneficial microbes into agro-ecosystems not only generates an increase in food production but also mitigates the economic, social, and environmental issues of intensive non-sustainable agriculture. In this way, the isolation, characterization, and exploitation of preserved beneficial microbes in microbial culture collections (MCC) is crucial for the ex situ maintenance of native soil microbial ecology focused on driving sustainable food production. This review aims to provide a critical analysis of the current and future role of global MCC on sustainable food security, as providers of a large number of beneficial microbial strains with multiple metabolic and genetic traits.